Efficacy and safety of left bundle branch area pacing versus right ventricular apex pacing in patients with atrioventricular block: study protocol for a randomised controlled trial. Issue 6 (22nd June 2021) - Wang, Zefeng; Du, Xiao; Cheng, Liting; Liang, Zhuo; Dong, Ruiqing; Hang, Fei; Chen, Jieruo; Wang, Xinlu; Wang, Ziyu; Chen, Junjun; Wu, Yongquan; Zhang, Junmeng
Abstract : Introduction: Left bundle branch area pacing (LBBaP) is a relatively new approach for physiologic pacing. A limited number of retrospective clinical studies, featuring small sample sizes, have shown that compared with right ventricular apex pacing (RVAP), the QRS duration of postoperative ECG in LBBaP patients is narrower and the cardiac systolic function is improved. However, there have been no randomised controlled trials (RCTs) evaluating the efficacy and safety of LBBaP in patients with atrioventricular block (AVB). Therefore, the current study intends to address the paucity in RCT data evaluating LBBaP versus RVAP in AVB patients. Analysis and methods: This study is a single-centre, randomised controlled superiority trial to be conducted at the Cardiac Centre of Beijing Anzhen Hospital. From January 2021 to December 2023, 210 consecutive AVB patients meeting the inclusion criteria and receiving pacemaker implantation will be enrolled. Participants will be randomly divided into an experimental group (LBBaP) and a control group (RVAP) at a 1:1 ratio. The primary outcome is left ventricular ejection fraction (LVEF), which will be assessed by echocardiography. The secondary outcomes in this study are synchrony of left ventricular systole, NT-proBNP, LVEDD, the 6-min walk distance, quality of life (SF-36 scale), all-cause mortality, cardiovascular death events, rehospitalisation rate and major complication rate. Ethics and dissemination: This study was approved by the Medical Ethics Committee of Beijing Anzhen Hospital (No. 2020021X). The results of the trial will be presented at national and international conferences. We hypothesise that compared with RVAP, LBBaP will be superior for treating patients with AVB. This trial will provide evidence-based suggestion for the majority of electrophysiologists in pacing implantation. Trial registration: ChiCTR2000034335.